Dampak Profesionalisme, Integritas, Kompetensi, dan Independensi pada Kualitas Audit di Kantor Akuntan Publik Provinsi Bali - Aprilianti, Ni Luh Rosa; Nyoman Badera, I Dewa (E-Jurnal Akuntansi; Vol 31 No 2 (2021)DO - 10.24843/EJA.2021.v31.i02.p16, 2021)
The quality of audits produced by public accountants is indeed under the spotlight of the public after several scandals involving public accountants, both from outside and from within the country. This study aims to determine the effect of professionalism, integrity, competence, and independence on audit quality at the Bali Province Public Accountant Office. This research was conducted in KAP Bali Province which is registered with IAPI totaling 16 KAP. The sample used was 118 auditors, with a saturated sampling method. Collecting data by distributing questionnaires with respondents who returned numbered 73 people. The analysis technique used is multiple linear regression. Based on the results of the analysis, it was found that professionalism, integrity, and independence had a positive effect on audit quality in KAP Bali Province. Meanwhile competence has no effect on audit quality in KAP Bali Province. Keywords: Professionalism; Integrity; Competence; Independence; Audit Quality.